The presence of the female Peruvian professional lawyer in the national life during the 1962-2012 period in the labor market and Law research - Vidal Cabeza de Tarazona, Gisela H. (2018)
This study aims to highlight the research carried out by female Peruvian lawyers in the Law field. It also mentions the positions in national and international public administration held bywomen, enabling women’s visibility in the Law field.